THE RELATIONSHIP OF STUDENTS’ PERCEPTIONS AND ATTITUDES TOWARDS ENVIRONMENTAL SANITATION IN PRIMARY SCHOOL NEGERI 2 KATOBENGKE, BAUBAU CITY - Marliana, Marliana; Jumadi, Jumadi; Muriman, La Ode Yusman; Amiruddin, Eky Endriana (HEARTY, 2024)
The attitude of students who throw their rubbish carelessly and students' perceptions regarding the sanitation of their environment, the lack of providing rubbish bins in classrooms and the school environment, and the lack of hand washing places with running water and soap.  The aim of the research was to determine the relationship between students' perceptions and attitudes towards environmental sanitation at SD Negeri 2 Katobengke, Baubau City.  This type of research is quantitative using a cross-sectional design.  The sample in this study was 120 students consisting of 41 elementary school students in class IV, 33 students in class V, and 46 class VI students.  Data analysis used univariate and bivariate analysis using the chi-square statistical test at a confidence level of 95% or α = 0.05.  The results of this research show that there is a relationship between students' perceptions of environmental sanitation with a significant value of p value = 0.001 <α = 0.05 and there is a relationship with students' attitudes towards environmental sanitation with a significant value of p value = 0.000 <α = 0.05.  In this research, there is a significant relationship between students' perceptions and attitudes towards environmental sanitation at SD Negeri 2 Katobengke, Baubau City.